Personal Protective Equipment Availability and Utilization Among Interventionalists - André Rose; William Ian Duncombe Rae (Elsevier, 2019)
Objective: This study explored personal protective equipment (PPE) availability and PPE utilization among interventionalists in the catheterization laboratory, which is a highly contextualized workplace. Methods: This is a cross-sectional study using mixed methods. Participants (108) completed a survey. A hyperlink was sent to the participants, or they were asked to complete a paper-based survey. Purposively selected participants (54) were selected for individual (30) or group (six) interviews. The interviews were conducted at conferences, or appointments were made to see the participants. Logistic regression analysis was performed. The qualitative data were analyzed thematically. Results: Lead glasses were consistently used 10.2% and never used 61.1% of the time. All forms of PPE were inconsistently used by 92.6% of participants. Women were 4.3 times more likely to report that PPE was not available. PPE compliance was related to fit and availability. Conclusions: PPE use was inconsistent and not always available. Improving the culture of radiation protection in catheterization laboratories is essential to improve PPE compliance with the aim of protecting patients and operators. This culture of radiation protection must include all those involved including the users of PPE and the administrators and managers who are responsible for supplying sufficient, appropriate, fitting PPE for all workers requiring such protection. Keywords: Gender parity in the workplace, PPE availability, PPE utilization, Quality of care